2011
DOI: 10.1016/j.icheatmasstransfer.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of heat transfer enhancement of nanofluids in an inclined lid-driven triangular enclosure

Abstract: The behavior of nanofluids is investigated numerically in an inclined lid-driven triangular enclosure to gain insight into convective recirculation and flow processes induced by a nanofluid. The present model is developed to examine the behavior of nanofluids taking into account the solid volume fraction δ. Fluid mechanics and conjugate heat transfer, described in terms of continuity, linear momentum and energy equations, were predicted by using the Galerkin finite element method. Comparisons with previously p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…They indicated that adding nanoparticles leads to rise in Nusselt number. Rahman et al [7] investigated nanofluid hydrothermal treatment in a tilted enclosure with moving wall. They proved that temperature enhances with rise of nanofluid volume fraction.…”
Section: Open Accessmentioning
confidence: 99%
“…They indicated that adding nanoparticles leads to rise in Nusselt number. Rahman et al [7] investigated nanofluid hydrothermal treatment in a tilted enclosure with moving wall. They proved that temperature enhances with rise of nanofluid volume fraction.…”
Section: Open Accessmentioning
confidence: 99%
“…Nanofluid technology is one specific area where a homogenous mixture of nanoparticles and a base fluid is used to develop nanofluids. Such fluids have vast applications in tribology [ 27 , 28 ], heat transfer enhancement [ 29 , 30 , 31 , 32 ], and biomedical filed [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since these fluids form a colloidal solution of the solid-liquid particles, therefore, the computational domain for nanofluids can be evaluated using either Eulerian or Lagrangian approach, depending upon the application. For a simplifying model, to minimize the computational effort, in engineering applications, like heat exchanger, the Eulerian approach is preferred [ 29 ]. However, in biomedical application, the Lagrangian approach is considered more effective, as the primary focus is on the study of Brownian motions and interaction of individual particles [ 33 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [39] investigated the impact of nanofluids in a base-heated isosceles triangular enclosure using a transient buoyancy driven condition. Laminar mixed convection in an inclined triangular cavity [40,41] using a Cu-water nanofluid has been performed. The authors claimed that the inclined angle plays an important role for the nanofluids in the heat exchange.…”
Section: Introductionmentioning
confidence: 99%